2002
DOI: 10.1046/j.1365-2427.2002.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and stability of lotic invertebrate communities in New Zealand

Abstract: 1. Persistence and stability of lotic invertebrate communities were determined at an annual time scale over a 9‐year period (1990–98) at 26 river sites over the northern half of New Zealand. In addition, a number of water quality variables were measured monthly and flow information collected continuously over the same period at each site. 2. The aim of the study was to describe the levels of interannual variability in invertebrate communities, and relate community changes to variability in environmental condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
93
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 37 publications
11
93
6
Order By: Relevance
“…Other studies have reported high variability in macroinvertebrate and fish communities under relatively constant environmental conditions (Moyle and Vondracek, 1985;Townsend et al, 1987;Weatherley and Ormerod, 1990;Scarsbrook, 2002;Milner et al, 2006). Our results suggest that variability in environmental factors was not detected due to characteristics of the water body.…”
Section: Discussioncontrasting
confidence: 43%
“…Other studies have reported high variability in macroinvertebrate and fish communities under relatively constant environmental conditions (Moyle and Vondracek, 1985;Townsend et al, 1987;Weatherley and Ormerod, 1990;Scarsbrook, 2002;Milner et al, 2006). Our results suggest that variability in environmental factors was not detected due to characteristics of the water body.…”
Section: Discussioncontrasting
confidence: 43%
“…Stability is defined as the degree of constancy in numbers, or relative abundance of organisms, whereas persistence refers to the continued presence of particular species in a community (Holling 1973;Connell and Sousa 1983;Scarsbrook 2002;Milner et al 2006;Collier 2008). Construction of the Three Gorges Reservoir (TGR) led to anthropogenic perturbations in local streams and a changed the stream environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, relationships between changes in environmental conditions and changes in community stability and persistence are relatively complex. Scarsbrook et al (2002) studied macroinvertebrate communities in New Zealand over a nine-year period and showed that persistence and stability were significantly related to the flow conditions, while there was no significant response to water quality changes. Brown et al (2006) showed that in alpine streams water quality variables (water temperature and suspended sediment concentration) were more important to stability than water quantity because of taxa possessing adaptations to flow variability.…”
Section: Introductionmentioning
confidence: 99%
“…Results from the available long-term hydroecological studies indicate that instream communities are influenced by variations in both the climatological (Bradley and Ormerod, 2001;Daufresne et al, 2003;Scarsbrook et al, 2003) and hydrological regimes (e.g., Lamouroux et al, 2006;Monk et al, 2006, Scarsbrook, 2002Wagner and Schmidt, 2004;Wood et al, 2001). However, attempts to quantify macroinvertebrate community response to river flow variability, and in particular high and low flows, are currently limited in terms of their temporal (typically <5 years study period) and/or geographical coverage (e.g., Caruso 2002;Clausen and Biggs, 1997;Sheldon and Thoms, 2006;Suren and Jowett, 2006).…”
Section: Introductionmentioning
confidence: 99%